Relationship between Personality Type and Academic Achievement of Korean Medical Students - Jang, Jae Soon; Hwang, Wei Wan; Cho, Seung Hun (Korean Journal of Oriental Physiology & Pathology, 2016)
The purpose of this study is to examine the relationship between Myers-Briggs Type Indicator(MBTI) personality type and academic achievement of Korean medical students. A total of 97 (57 men, 40 women; ages 24 to 36) fourth-year Korean medical students participated in this study. The MBTI questionnaire was administered to all the students for identification of their personality type and academic performance. The results are as follows. First, the proportions of Personality type of Korean medical students were Extroversion (E) 33.0% - Introversion (I) 67.0%, Sensing (S) 70.1%- Intuition (N) 29.9%, Thinking (T) 58.8%- Feeling (F) 41.2%, and Judging (J) 54.6% - Perceiving (P) 45.3%. Second, the most common personality type was ISTJ (22.7%), followed by ISTP (13.4%), ISFJ (12.3%). Third, according to the analysis of this study, academic achievement was significantly related with their personality type in the preference : Sensing (S) - Intuition (N) and Judging (J)-Perceiving (P). In analysis of Sensing (S) - Intuition (N) and Judging (J)-Perceiving (P) index, Sensing (S) and Judging (J) type students had higher academic achievement than Intuition (N) and Perceiving (P) type students. This is the study to identify the characteristics of MBTI in Korean Medical students. The findings indicate that academic achievement was significantly related to their personality type in the preference. Using the results of MBTI in Korean medical students, is helpful in selection of appropriate teaching and learning strategies to provide better education. KCI Citation Count: 0